Dampak Bayangan Pada Panel Surya Terhadap Daya Keluaran Photovoltaic - Samsurizal .; Sungsang Dody Purwanto; Miftahul Fikri; Christiono Christiono (Fakultas Teknik Elektro - Universitas Sultan Ageng Tirtayasa, 2020)
The effect of shadows that occur naturally due to the movement of the sun so that the radiance is exposed to trees and buildings before getting to the surface of the solar panels certainly affects the output power produced in the hydropower of the hydropower. This study used photovoltaic type polycrystalline, with observation data conducted in the campus environment IT-PLN. From the results of the study obtained that the power of 51.75 Watts occurred at 11.30 WIB, but when taken into account in real data the output power was obtained by 29.49 Watts at its peak power, it meant the shadow effect occurred by 84.217% at 12.30 WIB. Based on this, there can be a decrease in power by 43,582 Watts while when using the calculation of output power in real data there is a decrease of 25,155 Watts with a large shadow effect of 85,311% can be inferred the greater the shadow value that occurs the less power generated by a solar panel.